2017
DOI: 10.2478/iclr-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Is the Inter-American Human Rights System Biased? A Quantitative Analysis of Regional Human Rights Litigation in the Americas

Abstract: SummaryAlthough the Organization of American States’ Inter-American human rights system has played a key role in the advancement of human rights, its work has recently become controversial. Some leftist governments have alleged bias, criticizing the system as a politicized one that prioritizes certain rights over others and embodies a neoliberal ideology that reflects disproportionate US influence. The system has also faced perceptions of cultural bias from Anglophone Caribbean states. This article tests the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…For each case, the per capita gross domestic product of the state in question in the year in which the alleged violations occurred (in 2020 US dollars) was used as the measure of the state's level of economic development. Previous analysis of merits decisions found that states with higher per capita GDPs were significantly less likely to be found responsible for human rights violations (Zschirnt 2017). This is consistent with a large body of research linking economic development to democratization and the maintenance of effective systems of human rights protection (see, e.g., Przeworski et al 2000;Inglehart and Welzel 2005;Epstein et al 2006).…”
Section: Adjusted Per Capita Gdpsupporting
confidence: 68%
See 4 more Smart Citations
“…For each case, the per capita gross domestic product of the state in question in the year in which the alleged violations occurred (in 2020 US dollars) was used as the measure of the state's level of economic development. Previous analysis of merits decisions found that states with higher per capita GDPs were significantly less likely to be found responsible for human rights violations (Zschirnt 2017). This is consistent with a large body of research linking economic development to democratization and the maintenance of effective systems of human rights protection (see, e.g., Przeworski et al 2000;Inglehart and Welzel 2005;Epstein et al 2006).…”
Section: Adjusted Per Capita Gdpsupporting
confidence: 68%
“…Previous analysis of merits decisions found that states scoring higher on the Polity and CIRI indices were significantly less likely to be found responsible for human rights violations (Zschirnt 2017). This is consistent with analyses of petitions filed in the European human rights system and with the United Nations Human Rights Committee, which have found that states with higher levels of democratization and human rights protection have had fewer petitions filed against them and have been less likely to be found responsible for human rights violations when they have been the subjects of petitions (Boyle and Thompson 2001;Cole 2006Cole , 2011.…”
Section: Ciri Human Rights Index Scorementioning
confidence: 93%
See 3 more Smart Citations